The effect of tourism business employees’ cyberloafing behaviors and business motivations on the organizational identification - Kerem Kaptangil; Kübra Asan; Aysun Gargaci Kinay (Tourism & Management Studies)
With the development of communication technologies, “Cyberloafing”, which means the use of tools such as telephone, tablet, internet for business purposes or individual purposes, has become a subject of debate. From this point of view, the cyberloafing behavior of the employees in tourism enterprises was examined. In the study, it was aimed to investigate the effects of cyberloafing behavior of employees on business motivations and organizational identification in tourism businesses. For this purpose, field research was conducted on 8 hotel management employees in Sinop and Samsun provinces. The data collected through the questionnaire were analyzed by factor analysis and partial least squares structural modeling (PLS). Findings indicate that cyberloafing is partially and relatively low impact on job motivation and organizational identification. The results of the study contribute to the organizational behavior literature in the context of cyberloafing, and offer suggestions for hotel managers.